Effects of Adrenal Glucocorticoids on Polyoma Virus Replication - Morhenn, Vera (1973)
Treatment of polyoma virus-infected fibroblasts from mouse embryos and virus-infected 3T3 cells with physiological concentrations of the glucocorticoids enhances plaque formation at least 10-fold. The data suggest that this effect results from an increased rate of virus production. Steroid specificity studies indicate that the cytoplasmic receptors that mediate the physiological actions of these hormones are also involved in the present effect.